Is it Possible to Design a Battery as Bio-Fuel Cells for Charging the Smart Phone using Thermal Radiation of Human Body? A New Proposal - Lin, Jyh-Woei (International Journal of Computer (IJC), 2022)
All objects including the human body emit electromagnetic radiation, whose wavelength is related to the temperature of the object, so this radiation is sometimes called thermal radiation. A smart phone is a computing platform portable device, which combines mobile telephone and computing functions e.g. video, cameras, and gaming. Usually the temperature of human body is stable, so that the amount of thermal radiation is also stable. A battery can be designed and is used in the smart phone, then, anytime it will be convenient to charge the battery as bio-fuel cells with stable amount of thermal radiation. It is a new proposal in this study.